2023
DOI: 10.3389/fvets.2023.1284523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented feed on growth performance, serum biochemical indexes, antioxidant capacity, and intestinal health of lion-head goslings

Zhiqi Fu,
Na Ao,
Xiaoen Liang
et al.

Abstract: IntroductionThe aim of this study was to evaluate the effects of fermented feed on growth performance, antioxidant indexes and intestinal health in lion-head goslings.Methods288 male lion-head goslings (one-day-old) were randomly divided into four groups (6 replicates per group, 12 samples per replicate): control group (basal diet) and fermented feed (FF) groups (basal diet supplemented with 2.5, 5.0 and 7.5% FF, respectively). The experimental period lasted 28 days.ResultsThe results showed that 5.0 and 7.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Therefore, the effective control of oxidative stress is essential to maintaining animal health and improving breeding efficiency [ 11 ]. Research has shown that the supplementation of fermented feed can effectively help maintain the stability of the intestinal environment and reduce the adverse effects of oxidative stress [ 12 , 13 ]. For example, Jairath et al [ 14 ] found that fermentation also resulted in a significant increase in antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effective control of oxidative stress is essential to maintaining animal health and improving breeding efficiency [ 11 ]. Research has shown that the supplementation of fermented feed can effectively help maintain the stability of the intestinal environment and reduce the adverse effects of oxidative stress [ 12 , 13 ]. For example, Jairath et al [ 14 ] found that fermentation also resulted in a significant increase in antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%